Large-scale production of (GeTe)x(AgSbTe2)100−x (x=75, 80, 85, 90) with enhanced thermoelectric properties via gas-atomization and spark plasma sintering. (15th April 2017) - Kim, Hyo-Seob; Dharmaiah, Peyala; Madavali, Babu; Ott, Ryan; Lee, Kap-Ho; Hong, Soon-Jik
Abstract: (GeTe) x (AgSbTe2 )100− x : TAGS thermoelectrics are an attractive class of materials due to their combination of non-toxicity and good conversion efficiency at mid-temperature ranges. In the present work, we have utilized energy and time efficient high-pressure gas atomization and spark-plasma sintering techniques for large-scale preparation of samples with varying composition (i.e., (GeTe) x (AgSbTe2 )100− x where x  = 75, 80, 85, and 90). High-temperature x-ray diffraction was used to understand the phase transformation mechanism of the as-atomized powders. Detailed high-resolution transmission electron microscopy of the sintered samples revealed the presence of nanoscale precipitates, antiphase, and twin boundaries. The nanoscale twins and antiphase boundaries serve as phonon scattering centers, leading to the reduction of total thermal conductivity in TAGS-80 and 90 samples. The maximum ZT obtained was 1.56 at 623 K for TAGS-90, which was ∼94% improvement compared to values previously reported. The presence of the twin boundaries also resulted in a high fracture toughness (KIC ) of the TAGS-90 sample due to inhibition of dislocation movement at the twin boundary. Graphical abstract: Improved figure of merit, ZT of TAGS- x ( x  = 75, 80, 85, and 90) materials by Gas atomization and spark plasma sintering (our process) and, comparison of the present ZT with existing literature. Image 1